Effect of SNPs in HSP Family Genes, Variation in the mRNA and Intracellular Hsp Levels in COPD Secondary to Tobacco Smoking and Biomass-Burning Smoke - Ambrocio-Ortiz, Enrique; Pérez-Rubio, Gloria; Ramírez-Venegas, Alejandra; Hernández-Zenteno, Rafael; Del Angel-Pablo, Alma D.; Pérez-Rodríguez, Martha E.; Salazar, Ana M.; Abarca-Rojano, Edgar; Falfán-Valencia, Ramcés (Frontiers in Genetics, 2020)
HSP genes are a super-family responsible for codifying high conserved proteins, important for antigenic presentation, immune response regulation, and cellular housekeeping process. These proteins can be increased by cellular stress related to pollution, for example, smoke-related to biomass burning and/or tobacco smoking. SNPs in these genes could affect the level proteins, as well as the susceptibility to develop lung diseases, like COPD, related to the exposition of environmental factors. Methods: Subjects included were organized in two comparison groups; 1,103 smoker subjects (COPD patients, COPD-S=360; without COPD, SWOC=743) and 442 never smokers, chronically exposed subjects to biomass smoke (COPD patients, COPD-BS=244; exposed without COPD, BBES=198). Eight SNPs in three HSP genes were selected and genotyped, four in HSPA1A, two for HSPA1B y two in HSPA1L. Sputum expectoration was induced in order to obtain pulmonary cells and relative quantification of mRNA expression. Subsequently, the intracellular protein levels of total Hsp27, phosphorylated Hsp27 (Hsp27p), Hsp60, and Hsp70 were measured in a sample of 148 selected individuals based on genotypes. Results: In smokers’ group, by a dominant model analysis, we found associations between rs1008438 (CA+AA; p=0.006, OR=1.52), rs6457452 (CT+TT; p=0.000015, OR=1.99) and rs2763979 (CT+TT; p=0.007, OR=1.60) and the risk to COPD. Among exposed to biomass-burning smoke, only the rs1008438 (CA+AA; p<0.01, OR=2.84) was found associated. Additionally, rs1008438 was associated with the severity in the COPD-S group (AA; p=0.02, OR=2.09). An increase in the relative expression levels of HSPA1A was found (12-folds change) in COPD-BS than in BBES group. Differences in Hsp27 and Hsp60 levels were found (p<0.05) in the comparison of COPD-S vs. SWOC. In the biomass-burning smoke-exposed, differences in the levels for all proteins (p<0.05) were detected. Conclusion: SNPs in HSP genes are associated with the risk to COPD and severe forms of the disease. Differences in the intracellular Hsp levels are altered depending on exposition to biomass-burning smoke or tobacco smoking.